HOMEODOMAIN PROTEIN 1 is required for jasmonate‐mediated glandular trichome initiation in Artemisia annua. Issue 3 (23rd September 2016) - Yan, Tingxiang; Chen, Minghui; Shen, Qian; Li, Ling; Fu, Xueqing; Pan, Qifang; Tang, Yueli; Shi, Pu; Lv, Zongyou; Jiang, Weimin; Ma, Ya‐nan; Hao, Xiaolong; et al.
Summary: Glandular trichomes are generally considered biofactories that produce valuable chemicals. Increasing glandular trichome density is a very suitable way to improve the productivity of these valuable metabolites, but little is known about the regulation of glandular trichome formation. Phytohormone jasmonate (JA) promotes glandular trichome initiation in various plants, but its mechanism is also unknown. By searching transcription factors regulated by JA in Artemisia annua, we identified a novel homeodomain‐leucine zipper transcription factor, HOMEODOMAIN PROTEIN 1 (AaHD1), which positively controls both glandular and nonglandular trichome initiations. Overexpression of AaHD1 in A. annua significantly increased glandular trichome density without harming plant growth. Consequently, the artemisinin content was improved. AaHD1 interacts with A. annua jasmonate ZIM‐domain 8 (AaJAZ8), which is a repressor of JA, thereby resulting in decreased transcriptional activity. AaHD1 knockdown lines show decreased sensitivity to JA on glandular trichome initiation, which indicates that AaHD1 plays an important role in JA‐mediated glandular trichome initiation. We identified a new transcription factor that promotes A. annua glandular trichome initiation and revealed a novel molecular mechanism by which a homeodomain protein transduces JA signal to promote glandular trichome initiation. Our results also suggested a connection between glandular and nonglandular trichome formations.